Cambios estructurales durante la pirólisis y la gasificación del carbón de Venecia con CO2 a alta presión (2007)
ABSTRACT: The process of coal pyrolysis and gasification coal comprises the decomposition of the coal macromolecular network, which can be influenced by the temperature, the pressure and the composition of the gas of reaction. In the present investigation, the effect of the pressure was studied in the process of pyrolysis and the gasification with CO 2 of Venecia coal. The pressure effect was studied to determine the effect of the changes of the textural properties in the adsorption of gases (N 2 CO 2 ) as well as the changes in morphology by SEM. The results indicate that the pressure does not have a significant effect in the production of volatile material and that the main structural change is in the micropore volume and the internal surface area, which decreases with the increase in the pressure. The Venecia coal gasification experiments with CO 2 at 1 bar and 10 bar showed activation energies of 250 kJ/mol and 163 kJ/mol respectively and that the best model that can be used to for both conversions at these pressures of reaction is the modified volumetric model.